Adult immuno-oncology: using past failures to inform the future. Issue 9 (11th May 2020) - Rahman, Maryam; Sawyer, W Gregory; Lindhorst, Scott; Deleyrolle, Loic P; Harrison, Jeffrey K; Karachi, Aida; Dastmalchi, Farhad; Flores-Toro, Joseph; Mitchell, Duane A; Lim, Michael; Gilbert, Mark R; Reardon, David A
Abstract: In oncology, "immunotherapy" is a broad term encompassing multiple means of utilizing the patient's immune system to combat malignancy. Prominent among these are immune checkpoint inhibitors, cellular therapies including chimeric antigen receptor T-cell therapy, vaccines, and oncolytic viruses. Immunotherapy for glioblastoma (GBM) has had mixed results in early trials. In this context, the past, present, and future of immune oncology for the treatment of GBM was discussed by clinical, research, and thought leaders as well as patient advocates at the first annual Remission Summit in 2019. The goal was to use current knowledge (published and unpublished) to identify possible causes of treatment failures and the best strategies to advance immunotherapy as a treatment modality for patients with GBM. The discussion focuses on past failures, current limitations, failure analyses, and proposed best practices moving forward.